Design of the large hadron electron collider interaction region - E. Cruz-Alaniz; D. Newton; R. Tomás; M. Korostelev (Physical Review Special Topics. Accelerators and Beams, 2015)
The large hadron electron collider (LHeC) is a proposed upgrade of the Large Hadron Collider (LHC) within the high luminosity LHC (HL-LHC) project, to provide electron-nucleon collisions and explore a new regime of energy and luminosity for deep inelastic scattering. The design of an interaction region for any collider is always a challenging task given that the beams are brought into crossing with the smallest beam sizes in a region where there are tight detector constraints. In this case integrating the LHeC into the existing HL-LHC lattice, to allow simultaneous proton-proton and electron-proton collisions, increases the difficulty of the task. A nominal design was presented in the the LHeC conceptual design report in 2012 featuring an optical configuration that focuses one of the proton beams of the LHC to β^{*}=10  cm in the LHeC interaction point to reach the desired luminosity of L=10^{33}  cm^{-2} s^{-1}. This value is achieved with the aid of a new inner triplet of quadrupoles at a distance L^{*}=10  m from the interaction point. However the chromatic beta beating was found intolerable regarding machine protection issues. An advanced chromatic correction scheme was required. This paper explores the feasibility of the extension of a novel optical technique called the achromatic telescopic squeezing scheme and the flexibility of the interaction region design, in order to find the optimal solution that would produce the highest luminosity while controlling the chromaticity, minimizing the synchrotron radiation power and maintaining the dynamic aperture required for stability.